1973
DOI: 10.1017/s0043174500031878
|View full text |Cite
|
Sign up to set email alerts
|

Common Chickweed Control in Established Alfalfa

Abstract: Herbicide treatments were applied to established alfalfa (Medicago sativaL.) in 1969 and 1970 to determine winter annual weed control efficacy, crop tolerance, and influence on alfalfa yield and protein. Common chickweed (Stellaria media(L.) Cyrillo) was the predominant species in both years. Excellent weed control was achieved in 1969 with 2-sec-butylamino-4-ethylamino-6-methoxy-s-triazine (GS 14254) at 1.7 kg/ha, 2-[[4-chloro-6-(ethylamino)-s-triazin-2-yl]amino]-2-methyl-propionitrile (cyanazine) at 4.5 kg/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Twelve of 23 herbicide treatments significantly increased first harvest alfalfa protein percentage in 1972. This is in con trast to the 1971 results and studies conducted by Kapusta (7) in 1969 and 1970. All triazine herbicides increased percent protein although not at all rates tested.…”
Section: Downy Brome Yields As Affected By Herbicide Treatmentssupporting
confidence: 85%
“…Twelve of 23 herbicide treatments significantly increased first harvest alfalfa protein percentage in 1972. This is in con trast to the 1971 results and studies conducted by Kapusta (7) in 1969 and 1970. All triazine herbicides increased percent protein although not at all rates tested.…”
Section: Downy Brome Yields As Affected By Herbicide Treatmentssupporting
confidence: 85%
“…In some studies, weed control has increased alfalfa yields (4,6,9); and in others, yields were similar or less following weed control (10,11). Results from several experiments have shown that herbicides can be used to control weeds selectively in established alfalfa (4,5,6,8,11).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of the 0.9 kgjha rate of simazine to control common ragweed should be of no practical concern, since it usually is intended for control of perennials, such as hoary alyssum, white cockle, and yellow rocket. Previous work by a number of researchers (4,7,8,9,12) has demonstrated the potential of all of these herbicides for controlling specific weed problems in alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…While the triazine herbicides have demonstrated a potential for controlling perennial weeds in alfalfa, these chemicals frequently injure the crop (4,7,8,12). This injury is often associated with young stands where taproot development is not complete, with sandy soils where excessive leaching of the herbicides 1 R•:search supported by the College of Agric.…”
mentioning
confidence: 99%